Placenta Percreta With Bladder Infiltration : A Case Report - Reinaldo, Poldo; Permana, Bayu; Syahredi, Syahredi (Fakultas Kedokteran Universitas Andalas, 2022)
Objective : To report a case of placenta percreta with bladder infiltration.Method : Case reports.Case :a 24-year-old female G2P1A0H1 gravid 26-27 weeks, placenta percreta with gross hematuria. The second pregnant patient was less months pregnant with the results of a fetal ultrasound examination with a placenta covering the uterine internum (OUI) and suspected of penetrating the uterine wall (percreta), and a cesarean hysterectomy was performed.Discussion : The cause of placenta percreta is unknown, it is associated with several clinical risk factors like the previous cesarean, placenta previa, grand multiparity, and previous uterine curettage. The management of placenta percreta can be challenging because the loss occurs at two sites in labor. Refractory hematuria occurs in 25% of patients due to placenta percreta invasion of the bladder. Management involves a team of obstetricians, urologists, intensivists, and neonatologists. Treatment is preferably carried out in tertiary care where there is a definite stock of blood with adequate blood products, a fully equipped neonatal intensive care unit (NICU). Delivery may be considered at 34-35 weeks gestation if there is no maternal and fetal deterioration because the incidence of antepartum hemorrhage appears to increase sharply at 36 weeks.Conclusion : Management is recommended for placenta percreta cases, planning for premature cesarean hysterectomy with placenta left in situ. However, the diagnosis is made based on the results of the anatomic pathology obtained after hysterectomy, and is not considered a first-line treatment for women who still wish to maintain future fertility.Keywords:placenta percreta, cesarean hysterectomy